Program Pembinaan Mental Spiritual Masyarakat Desa Bontokassi Melalui Pendekatan Tarbiah: Spiritual and Mental Development Program for the Bontokassi Village Community Through the Tarbiah Approach - Askar Patahuddin; Jujuri Perdamaian Dunia; Mirnawati; Munawar Khalil (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This community service program aimed to strengthen the mental and spiritual development of the people of Bontokassi Village through a Tarbiah-based approach emphasizing the cultivation of Islamic values, the habituation of religious practices, and community participation. The program consisted of five main activities: Dawn Religious Lectures (Kultum Subuh), Qur’anic Learning Centers for Children (TK/TPA), Weekly Qur’an Memorization Sessions (Tahfidz), Arabic Language Instruction and Ramadan Islamic Camp, and Ramadan Fest. The study employed a Participatory Action Research (PAR) approach, actively involving community members as partners throughout all stages of the program. Data were collected through participant observation, in-depth interviews, and document analysis conducted from March 15 to March 29, 2026. Data validity was ensured through source and technique triangulation, while qualitative data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing and verification. The findings indicate that the Tarbiah approach contributed to increasing religious awareness, strengthening discipline in worship, encouraging parental involvement in children’s religious education, and enhancing community engagement with the Qur’an. The program also broadened participants’ Islamic knowledge through Arabic language learning and intensive religious instruction. Furthermore, Ramadan Fest fostered social cohesion by promoting intergenerational collaboration in various educational and religious activities. The program’s success was supported by the active involvement of village authorities, community leaders, mosque administrators, TK/TPA instructors, youth organizations, and local residents. These findings suggest that a community-based Tarbiah approach can serve as an effective, adaptive, and sustainable model for strengthening the spiritual development and religious character of rural communities.